Coagulation studies in haemophilic patients taking oral contraceptives. Issue 1 (February 1971) - Bloom, A. L.; Beck, Peter; Giddings, J. C.; Sweetnam, P. M.
Abstract : Coagulation studies were performed on haemophilic patients during a controlled trial of oral contraceptive therapy. Treatment with a combined oestrogen-progestogen preparation was associated with a significant rise in the factor VII-X complex. This change was not observed during treatment with progestogen alone. The highest levels of factor IX and fibrinogen and the lowest levels of factor X were observed during the first period of the trial but these effects were independent of the type of treatment. The results suggest that the effects of oral contraceptives on blood coagulation in haemophilic males are similar to those observed in normal females and that the changes are due to the oestrogenic component.